Child development beyond the nutrition-specific models: bridging the pathways via psychosocial stimulation - David, Blessy E.; Kumar, Sanjay (Frontiers in Psychology, 2023)
Background Undernutrition has severe and lasting consequences on child development. Evidently, the interventions based on the biomedical model with food and direct supplementation have failed to produce the desired outcomes for decades. In light of the established positive effects of psychosocial stimulation on developmental outcomes, we propose that the observed failures relate to not including psychosocial stimulation within the interventions. Here we test whether psychosocial stimulation mediates the association between nutritional status and motor and mental development in a large cohort from Madhya Pradesh, India. Method Using a correlational design in children below 3 years of age (N = 275; Males = 148, Females = 127) nutritional status was measured through mid-upper arm circumference (MUAC), psychosocial stimulation was assessed with the HOME-inventory, and motor and mental development were assessed with the Developmental Assessment Scales for Indian Infants (DASII). We assessed the effectiveness of 25-week intervention model incorporating psychosocial stimulation on 95 undernourished children in experimental group and 77 in control group. Results The study found that psychosocial stimulation fully mediated the relationship between nutritional status and the motor development [Effect = 1.03, 95% C.I. (0.19, 2.04), p = 0.05] and mental development [Effect = 0.49, 95% C.I. (0.09, 1.03), p = 0.05] in children under 3 years of age. Nutritional status significantly predicted the psychosocial stimulation to the child (R2 = 0.77). Analyzing the effectiveness of the intervention program revealed significant reduction in the developmental delays in both the motor [t(81) = 2.568, p = 0.012] and mental development [t(81) = 4.506, p = 0.001] of the undernourished children. Conclusion Findings indicate that nutrition translates into positive developmental outcomes in a child only with the scaffolding effects of psychosocial stimulation primarily received from home. Integrating psychosocial stimulation activities like storytelling, play, art and crafts, puppets, travel etc. in the intervention programs designed to address undernutrition may yield rich dividends in bridging the developmental delays among undernourished children.